Comparison of the Effects of Hugo’s Point Massage and Play on IV-Line Placement Pain in Children: A Randomized Clinical Trial - Shahnaz Salawati Ghasemi; Mehdi Beyramijam; Fatemeh Yarahmadi; Taban Nematifard; Seyed Shahabeddin Bahrani; Masoomeh Khaleghverdi (Pain Research and Management)
Reduction of intravenous line placement pain is one of the most important nursing priorities in the pediatric wards. The present study was aimed at comparing the effect of Hugo’s point massage and play on the severity of IV-line placement pain in hospitalized children aged 3–6 years in the pediatric ward. 72 children were selected and assigned randomly to three groups, i.e., control, play, and Hugo point massage. In the massage group, the middle angle between the first and second bones of the palm of the opposite hand was massaged, and the playgroup encouraged bubble-making play. The one-way analysis of variance (ANOVA) did not show a statistically significant difference between the mean IV-line placement pain in play, Hugo’s point, and control groups before interventions (p=0.838; p>0.05). However, the ANOVA test revealed a significant difference between the mean IV-line placement pain in play, Hugo’s point, and control groups after the interventions (p=0.006; p<0.05). The result of the post hoc Scheffe test also showed a statistically significant difference between the mean intensity of IV-line placement pain in both play therapy and Hugo’s point massage groups (p=0.028; p<0.05). Moreover, this test showed that the playgroup children felt less pain than Hugo’s point and control group children. This study showed that, in comparison with Hugo’s point massage, the play was a more effective way for reducing pain caused by IV-line placement in children, and pediatric nurses can play a significant role in reducing and managing children’s pain by using it.